Kepemilikan Aset, Akses Modal dan Kualitas Sumber Daya Manusia Terhadap Tingkat kemiskinan Di Sumatera - Putri, Vani Yulia; Yulhendri, Yulhendri (Jurnal E-Bis, 2025)
Poverty is a condition of deprivation experienced by individuals, which directly impacts their well-being and is a fundamental problem that is difficult to overcome in all countries in the world, including Indonesia. This study analyzes the impact of asset ownership, capital access, and human resource quality on poverty rates in Sumatra. Using an associative approach with panel data regression and EViews 12, this study examines secondary data from 10 Sumatran provinces (2019-2023) sourced from the Central Bureau of Statistics and Bank Indonesia. Data collection uses documentation, and the Fixed Effects Model is applied for analysis. The results show that asset ownership and human resource quality significantly influence poverty rates individually, while capital access does not have a significant partial effect. However, collectively, asset ownership, capital access, and human resources significantly influence poverty rates in Sumatra.